Prediction of Bankruptcy Risk Using Financial Distress Analysis - Rachma Sari, Kartika; Martini, Rita; Almira, Nadya; Hartati, Sukmini; Husin, Farida (Manunggal Halim Jaya, 2022)
Financial distress analysis using X-Score Zmijewski model, Z-Score Altman model, and S-Score model Springate is intended to determine the potential for bankruptcy at PT. Hero Supermarket, Tbk. Secondary data was used in the 2016-2020 financial statements. The results of the calculation of the X-Score method from 2016 - 2019 were in a non-financial distress condition, but in 2020 they were in a distressed situation. This follows the X-Score principle, which focuses on the company's liabilities. We decrease the safe zone to the danger zone from the Z-Score method. In the S-Score process, the company can go bankrupt. The analysis results of the three ways conclude that the company is experiencing financial difficulties. Fast and appropriate handling is needed to fix its condition, and management must improve financial performance. Company management must improve financial conditions, significantly reducing total liabilities every year. The actual existing company liabilities are not more significant than the income earned, so that the level of losses that will be experienced will be reduced. Furthermore, the company should conduct a company evaluation of efforts to improve operational and financial performance as response to the company’s financial condition. So that, the economic distress experienced can be appropriately resolved.